The Effect of Salt Consumption and Obesity on the Event of Primary Hypertension in the Work Area of Poleang Community Health Centers - Erniyanti; Asnia Zainuddin; Laode Muhammad Sety, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
One of the health problems that are often faced by the Indonesian people today is the problem of degenerative diseases. There has been a change in disease patterns in the community from infectious diseases to non-infectious diseases, this is marked by an increase in the number of sufferers from year to year. This can be seen from the 2018 regional Health Research data that the number of hypertension cases in Indonesia is 34.1%. The purpose of this study was to determine the effect of salt consumption and obesity on the incidence of primary hypertension in the work area of ??Poleang Health Center, Bombana Regency. This type of research is a survey with a retrospective approach, and uses a case control study design. The number of samples as many as 110 respondents with a purposive sampling technique. Data collection using questionnaires, measurement of weight and height. Data analysis using Chi Square test. The results showed that salt consumption and obesity were risk factors for primary hypertension in Poleang District, Bombana Regency. Suggestion; Increased socialization of Prolanis to patients with hypertension and optimization of posyandu for the elderly, early detection of hypertension and risk factors for hypertension. It is hoped that the community will adopt a healthy lifestyle, following the activities of the Community Health Center Chronic Disease Management Program.